Comparative Study of Serum Lipid Profile in Pre-eclampsia in a Tertiary Care Hospital, Bangladesh (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Objective: To estimate lipid profile in pre-eclampsia cases in Mymensingh Medical College Hospital.Materials and Methods: This cross sectional study was carried out in the dept. of Obstetrics and Gynaecology of Mymensingh Medical College and Hospital (MMCH) and outdoor Pathology Dept. of MMCH. A total 100 pregnant women were included in this study, out of which 50 were pre-eclampsia and 50 normal pregnant women. Purposive sampling technique was followed for selection of study population. Estimation of serum total cholesterol, triglyceride (TG), high density lipoprotein (HDL), low density lipoprotein (LDL) were done by colorometric method.Result: Findings of the study showed that woman with pre-eclampsia exhibits 14% higher mean plasma level of total cholesterol. It was (229.12 ± 49.31 mg/dl) in pre-eclampsia and (196.68 ± 38.60 ml/dl) in control group and the deference was statistically highly significant (p